The Role of Seed Breeder Farmer Groups in Increasing the Productivity of Paddy Rice in Seling Village Tabir Sub-District Merangin District - Fikriman Fikriman; Anjas Hari Laksana Sinaga; Asnawati Is Asnawati Is; Setiono Setiono (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research aims to determine the role of seed breeder farmer groups in increasing lowland rice productivity and to analyze the relationship between the role of seed breeder farmer groups and lowland rice productivity in Seling Village, Tabir District, Merangin Regency. The research was conducted from May 24, 2021, to June 24, 2021. The respondents in this research were members of the Seling Village Seed Breeding Farmer Group, totaling 82 people or 50% of the total population and using the proportional random sampling method. The data analysis method uses a Likert scale, mean, and Spearman Rank analysis. The research results show that the role of seed breeder farmer groups in increasing lowland rice productivity is high, with a total score of 2.37. It shows that there are learning classes with a score of 2.27, collaboration facilities with a score of 2.32, and production units with a score of 2.52. Furthermore, there is a strength of the relationship (correlation) between the variable role of the seed breeder farmer group and lowland rice productivity, which is 0.19754 or weak. From the T-test results, the t-count is 0.83859731 > t table 0.1829. This means there is a weak and significant positive relationship between the role of seed breeder farmer groups and the productivity of lowland rice farmers in Seling Village.